1979
DOI: 10.1161/01.cir.59.2.403
|View full text |Cite
|
Sign up to set email alerts
|

Univentricular heart of right ventricular type with double or common inlet.

Abstract: SUMMARY Seventeen cases are described in which both atria connect directly to a chamber with right ventricular characteristics. The atria connected through separate atrioventricular valves in six hearts and a common valve in 11. All hearts had a posterior rudimentary chamber. The septum which separated it from the main chamber was directed to the crux of the heart. Ten hearts were from patients with atrial situs solitus and seven from patients with atrial situs ambiguus. Arterial connections were concordant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

1982
1982
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 16 publications
0
22
1
Order By: Relevance
“…Smallhorn et al [5] reported that free-floating and large anterior leaflets, flanked by two lateral leaflets, are typical in patients with univentricular heart. Keeton et al [3] reported that papillary muscles arising from a rudimentary chamber are hypoplastic in patients with univentricular hearts of the right ventricular type with a common atrioventricular valve. In our series, two papillary muscles from the anterior leaflets were tightly attached to several chordae in all hearts, whereas few papillary muscles from the lateral or posterior leaflets were attached to the chordae.…”
Section: Discussionmentioning
confidence: 99%
“…Smallhorn et al [5] reported that free-floating and large anterior leaflets, flanked by two lateral leaflets, are typical in patients with univentricular heart. Keeton et al [3] reported that papillary muscles arising from a rudimentary chamber are hypoplastic in patients with univentricular hearts of the right ventricular type with a common atrioventricular valve. In our series, two papillary muscles from the anterior leaflets were tightly attached to several chordae in all hearts, whereas few papillary muscles from the lateral or posterior leaflets were attached to the chordae.…”
Section: Discussionmentioning
confidence: 99%
“…2 ' 3 It was on the basis of this conventional wisdom that a group of investigators from Europe, including the first author of this review, constructed formidable conventions to justify the existence of double inlet right ventricle as a "univentricular heart". 17 It came as somewhat of a surprise, therefore, to find this concept roundly criticised by Van Praagh and his colleagues, 8 since it was Van Praagh, albeit working with a different group of collaborators, who had first promoted the arrangement of double inlet as the defining feature for "single ventricle". 2 But the logic emphasised in their criticism, namely that "large right ventricle, together with small left ventricle, does not equal single ventricle", was inescapable.…”
Section: Ventricular Structure In the Setting Of Double Inlet Ventriclementioning
confidence: 99%
“…In patients with a dominant right ventricle, isomerism occurred in 18% and in those with a dominant left ventricle in only 2%. Not unexpectedly, a common AV valve was present in 77% of all cases with isomerism [2,13].…”
Section: Hearts With Ventricular Inversion a Dominant Left And An Unmentioning
confidence: 99%